Observation and properties of the X(3872) decaying to J/psi pi(+)pi(-) in p(p)over-bar collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, D. L.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. L.; Ahmed, S. N.; Ahn, S. H.; Alexeev, G. D.; et al. (American Physical Soc, 2004)
We report the observation of the X(3872) in the J/psipi(+)pi(-) channel, with J/psi decaying to mu(+)mu(-), in p (p) over bar collisions at roots=1.96 TeV. Using approximately 230 pb(-1) of data collected with the Run II D0 detector, we observe 522+/-100 X(3872) candidates. The mass difference between the X(3872) state and the J/psi is measured to be 774.9+/-3.1(stat)+/-3.0(syst) MeV/c(2). We have investigated the production and decay characteristics of the X(3872) and find them to be similar to those of the psi(2S) state.